Catalog of the Gerald K. Stone collection of Judaica : a bibliographical resource for Canadian Jewish studies - Stone, Gerald K., 1953- (North American Jewish Studies, 2020)
"Gerald K. Stone has collected books about Canadian Jewry since the early 1980s. This volume is a descriptive catalog of his Judaica collection, comprising nearly 6,000 paper or electronic documentary resources in English, French, Yiddish, and Hebrew. Logically organized, indexed, and selectively annotated, the catalog is broad in scope, covering Jewish Canadian history, biography, religion, literature, the Holocaust, antisemitism, Israel and the Middle East, and more. An introduction by Richard Menkis discusses the significance of the Catalog and collecting for the study of the Jewish experience in Canada. An informative bibliographical resource, this book will be of interest to scholars and students of Canadian and North American Jewish studies"--Provided by publisher.